Baicalin suppresses lung cancer growth phenotypes via miR-340-5p/NET1 axis. Issue 1 (1st January 2021) - Zhao, Fucheng; Zhao, Zhenxia; Han, Yanru; Li, Sujuan; Liu, Caili; Jia, Kui
ABSTRACT: As a malignant disease, lung cancer has a high morbidity and mortality rate. Baicalin is derived from Radix Scutellariae and has anti-tumor effects, however, its role in lung cancer remains unknown. Here, functional assays suggested baicalin suppressed in vitro lung cancer phenotypes. We used micro (mi)RNA array analysis to explore baicalin effects on miRNA expression. We observed baicalin increased miR-340-5p expression, whereas inhibition of this expression abolished anti-tumor effects of baicalin. Furthermore, neuroepithelial cell transforming 1 (NET1) functioned as a miR-340-5p target, and acted in a baicalin-dependent manner to regulate lung cancer progression. Thus, baicalin elicited antitumor activities by affecting the miR-340-5p/NET1 axis, suggesting a new approach to lung cancer clinical management.